2011
DOI: 10.7150/ijms.8.168
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Differential Gene Expression Profile in Peripheral Blood Cells of Patients with Human Essential Hypertension

Abstract: The polygenic nature of essential hypertension and its dependence on environmental factors pose a challenge for biomedical research. We hypothesized that the analysis of gene expression profiles from peripheral blood cells would distinguish patients with hypertension from normotensives. In order to test this, total RNA from peripheral blood cells was isolated. RNA was reversed-transcribed and labeled and gene expression analyzed using significance Analysis Microarrays (Stanford University, CA, USA). Briefly, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…ERAP1 is associated with chronic hypertension and a genetic variant shows reduced enzymatic activity, thus highlighting its role in blood pressure regulation [39, 40]. ERAP1 is also differentially expressed in essential hypertension [41]. ERAP2 shares similar functions with ERAP1 in blood pressure regulation and MHC I antigen presentation [42].…”
Section: Discussionmentioning
confidence: 99%
“…ERAP1 is associated with chronic hypertension and a genetic variant shows reduced enzymatic activity, thus highlighting its role in blood pressure regulation [39, 40]. ERAP1 is also differentially expressed in essential hypertension [41]. ERAP2 shares similar functions with ERAP1 in blood pressure regulation and MHC I antigen presentation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetics holds the key for efficient and radical treatments of hypertension since epidemiological studies have suggested that genetics accounts for 30 to 40% of blood pressure changes (Tanira and Al Balushi, 2005). Our previous microarray analysis on the differential gene expression between EH and normotensives identified 31 up-regulated and 18 down-regulated genes (Korkor et al, 2011), among which CD36 showed a 4.8-fold up-regulation and we have identified the +273A/G polymorphism of CD36 gene associated with hypertension (Liu et al, 2013). Besides, the expression of ERAP1 showed a 0.46-fold down-regulation with a P value ≤ 0.5%.…”
Section: Introductionmentioning
confidence: 98%
“…Korkor et al (45) 680 genes were found differentially expressed in untreated hypertensives compared to normotensive controls. On the other hand, only 7 genes were differentially expressed in treated hypertensives compared to normotensive controls.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, Korkor et al identified 49 differentially expressed genes; 31 up regulated and 18 down regulated genes. Amongst genes found to be altered include CD36, SLC4A1, NET1, SESN3, ZNF652, PRDX6, HIP1, FOLR3, ERAP1, CFD [45] . Most of the genes that were differentially expressed were related to immune/inflammatory responses.…”
Section: Altered Gene Expression In Bloodmentioning
confidence: 99%
See 1 more Smart Citation